The effect of financial literacy and entrepreneurship orientation on the performance of small-medium enterprise ‘tenun gringsing’ in tenganan village, karangasem regency - Ade Maharini Adiandari; Ni Luh Komang Purnama Yanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Small-medium business enterprises play an important role in the national economics. As such, the performance of small-medium enterprises should be optimized through various efforts among others; increasing financial literacy and entrepreneurship orientation of the businessman/woman themselves. The current research was conducted because there are some performance issues with the small-middle enterprise ‘Tenun Gringsing’ in Tenganan Village, Karangasem. In an effort to optimize and increase performance of the small-middle enterprise, there needs to be a competent financial literacy and a strong entrepreneurship orientation. The purpose of the current study is to study the effect of financial literacy and entrepreneurship orientation on the performance of small-medium enterprise “Tenun Gringsing” in Tenaganan Village Karangasem partially and simultaneously. This research applied a quantitative method. Population studied is 80 businesspeople of the small-medium “Tenun Gringsing” enterprise. Saturated sampling technique was used. Data was collected using interview, observation, survey, and documentation study methods. Data was analyzed using a Mutiple Regression Analysis. The results of the study indicated that there is a positive and significant effect (partially and simultaneously) of financial literacy (X1) and entrepreneurship orientation (X2) towards performance (Y).